Association of Dietary Patterns and CVD Risk Factors in Recently Diagnosed Type 2 Diabetes - R Hemalatha, P Amruth Rao, M Shiva Prakash; Ramulu, P.; Rao, P Sreevennala (International Journal of Innovative Research in Medical Science, 2017)
Significant association of dietary fat and CVD risk factor in recently diagnosed type-2 Diabetes was observed Aim: To study the association of dietary fat and CVD risk factors in recently diagnosed type-2 Diabetes. Materials and Methods: This is a hospital based cross-sectional study where 82 Diabetic subjects with newly diagnosed diabetes type 2, aged 20-50yrs, of both sexes and 68 Control subjects were recruited from the outpatient department of Osmania General Hospital. Patients were recruited after taking Institutes ethical committee approval and informed consent. Patients are on stable anti-diabetic medicines. Results: There is a significant association observed between diabetes status and consumption of vanaspati (dalda) and palm oil at 5% level of significance. A significant association also observed on the status of total cholesterol levels, TG level and LDL level with the diabetes. High prevalence of diabetes is observed for those who are having abnormal status of total cholesterol (>200mg/dl), TG (>150mg/dl), LDL (100mg/dl). The BMI status of the subject is not significantly associated with diabetes within three months, during this time BMI may not associated with diabetes. Empirical results showed that, subjects with chronic energy deficiency (CED) are non-diabetic (67%) and the subjects with overweight/obese are diabetic (54%) Conclusion: The intake of vanaspati (dalda) and palm oil is associated with the abnormalities of .lipid profile and HbA1C in recently diagnosed type-2 Diabetes.